Biodiversity and ecology of critically endangered, Ruens Silcrete renosterveld in the Buffeljagsrivier area, Swellendam - Groenewald, Johannes Philippus (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScConsEcol)--Stellenbosch University, 2014.